VizieR Online Data Catalog: 46 open clusters GaiaDR2 HR diagrams (Gaia Collaboration, 2018) - Gaia Collaboration; Babusiaux, C.; van Leeuwen, F.; Barstow; M., A.; Jordi, C.; Vallenari, A.; Bossini, A.; Bressan, A.; Cantat-Gaudin, T.; van Leeuwen, M.; Brown, A. G. A.; et al. (VizieR Online Data Catalog, 2018)
We have determined the membership of 46 open clusters. For the nine clusters within 250pc we determined optimised parallaxes based on the combined information extracted from the measured parallax and proper motion values. These clusters are : in Tables A1a & A3: alphaPer, Blanco1, ComaBer, Hyades, IC2391, IC2602, NGC2451A, Pleiades, Praesepe. The remaining 37 clusters are in Table A1b & A4: Coll140, IC4651, IC4665, IC4725, IC4756, NGC0188, NGC0752, NGC0869, NGC0884, NGC1039, NGC1901, NGC2158, NGC2168, NGC2232, NGC2323, NGC2360, NGC2422, NGC2423, NGC2437, NGC2447, NGC2516, NGC2547, NGC2548, NGC2682, NGC3228, NGC3532, NGC6025, NGC6281, NGC6405, NGC6475, NGC6633, NGC6774, NGC6793, NGC7092, Stock2, Trump02, Trump10. (4 data files).
Keywords: Clusters: open; Parallaxes: trigonometric; Proper motions